Bibliometric and visual analysis of nephrotoxicity research worldwide - He, Tianmu; Ao, Jingwen; Duan, Cancan; Yan, Rong; Li, Xiaomei; Liu, Liu; Zhang, Jianyong; Li, Xiaofei (Frontiers in Pharmacology, 2022)
Background: Nephrotoxicity of drugs contributes to acute kidney injury with high mortality and morbidity, which crucially limits the application and development of drugs. Although many publications on nephrotoxicity have been conducted globally, there needs to be a scientometric study to systematically analyze the intellectual landscape and frontiers research trends in the future. Methods: Publications on nephrotoxicity from 2011 to 2021 were collected to perform bibliometric visualization using VOSviewer, CiteSpace, and Scimago Graphica software based on the Web of Science Core Collection. Results: A total of 9,342 documents were analyzed, which were primarily published in the United States (1,861), China (1,724), and Egypt (701). For institutions, King Saud University (166) had the most publications; Food and Chemical Toxicology, PLOS One, and Antimicrobial Agents and Chemotherapy were productive journals, primarily concentrating on the mechanisms of nephrotoxicity and renoprotective in cisplatin and antibiotics, especially in oxidative stress. Burst detection suggested that cisplatin, piperacillin-tazobactam, vancomycin-induced nephrotoxicity, antioxidants, and new biomaterials are frontiers of research. Conclusion: This study first provides an updated perspective on nephrotoxicity and renoprotective strategies and mechanisms. This perspective may benefit researchers in choosing suitable journals and collaborators and assisting them in the deep understanding of the nephrotoxicity and renoprotective hotspots and frontiers.